"A Satisfaction to the Heart and to the Intellect". A Note on Osvald Sirén Connections with Italy through his Epistolary. - Antonella Perna (Finland, 2022)
Antonella Perna writes in her peer-reviewed article how her attention was drawn to the relationship and position of Osvald Sirén in Italian studies of Asian culture by a single letter in the Sirén Archive in Stockholm. According to that letter, Sirén was appointed Doctor Honoris Causa of the University of Rome La Sapienza. To Perna this single letter was not sufficient to explain why this happened and she started to look for other evidence to find out why he was honoured this way. Perna found the evidence in the correspondence of Sirén with the Italian scholar of Asian studies, Giuseppe Tucci. Perna is revealing new knowledge of this relationship. She writes: ‘since there are no previous studies on the relationship with Tucci, I would like to present a first analysis of unpublished letters and other archival material that can throw some light on this aspect of Sirén’s professional life: his particular role in the development of Oriental scholarship in Italy.’